Etika dan Profesi Kejaksaan dalam Perspektif Hukum : Studi Kasus Penyuapan Oleh Jaksa Pinangki - Shelomita Putri Amelia; Elirica Aliyah Irwan Bauw; Muhammad Regan Syahrendra; Ruben Nicholas Alfredo Tobing; Mulyadi Mulyadi (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This research aims to analyze the ethical and professional dilemmas within the prosecutorial institution, particularly concerning the bribery case involving Prosecutor Pinangki Sirna Malasari. The study focuses on the legal implications and systemic impacts of the ethical violations committed by law enforcement officials. A case study methodology with a qualitative analysis approach was employed, including document reviews, court rulings, and media coverage. The findings indicate that the bribery actions of Prosecutor Pinangki reflect a degradation of integrity and professionalism within the prosecution service, potentially undermining public trust in the criminal justice system. Furthermore, this study identifies gaps in oversight and weak enforcement of internal ethical codes as contributory factors to the violations. The implications of this case extend beyond legal aspects, impacting social and political dimensions, given the central role of the prosecution in upholding the rule of law. The conclusion emphasizes the necessity for comprehensive reforms in recruitment, promotion, and oversight systems within the prosecution service, alongside heightened awareness regarding the importance of professional ethics for every prosecutor. This study recommends strengthening both internal and external control mechanisms and imposing strict sanctions for any ethical violations to restore public trust and maintain the integrity of the prosecutorial institution.